Review of Ototoxic Drugs Using Health Insurance Data: A Data‐Driven Management System - Jiwon Kim; Chul Young Yoon; Junhun Lee; Young Joon Seo (OTO Open)
Abstract Objective With more than 1.57 billion people affected by hearing loss worldwide, this study investigates the association between ototoxic drug use and hearing loss, utilizing South Korean national health data. The goal is to inform clinical prevention and management guidelines by identifying ototoxic drugs and assessing their risks. Study Design This study is a retrospective observational study using the Health Insurance Review and Assessment Service (HIRA) to analyze the association between suspected ototoxic drug use and hearing loss. Setting Data were obtained from the National Patient Samples (NPS) of HIRA in South Korea, covering 2009 to 2016. The study included all National Health Insurance (NHI) enrollees with at least one hospital visit. Methods Patients diagnosed with suspected ototoxicity hearing loss (SOHL) were identified, and ototoxic drugs were reviewed using national data. Of 491 reviewed ingredients, 151 were suspected ototoxic. Logistic regression and Cox proportional hazards models assessed associations between drug prescriptions and SOHL, analyzed with SAS 9.4. Results SOHL patients were older, with higher rates of underlying conditions and medication use compared to controls. The odds ratio (OR) for SOHL was significantly elevated in patients aged ≥65, increasing from 3.007 to 3.366. Proton pump inhibitors (PPIs) and antibiotics presented elevated risks, especially in older adults, with hazard ratios (HRs) for PPIs rising from 1.85 to 2.90. Notably, PPIs posed higher risks for patients <65. Conclusion The study confirms that factors like age, gender, underlying diseases, and specific medications increase SOHL risk, emphasizing the need for cautious medication use tailored to age.